2022
DOI: 10.1021/acsanm.2c01100
|View full text |Cite
|
Sign up to set email alerts
|

Black TiO2 Nanotube Array/BiVO4 Heterojunction Photocatalysts for Tetracycline Removal with High Solution Detoxification Efficiency

Abstract: Pulsed laser deposition was employed to accurately vary the BiVO4 content on the outermost surface of black TiO2 (B-TiO2) nanotube arrays. The optimal B-TiO2(225) led to >80% tetracycline (TC) antibiotic removal, while only 27% TC removal was obtained by bare TiO2 nanotubes after 300 min of photocatalytic reaction under visible-light irradiation. Moreover, the removal rate constant using the optimal heterojunction sample was 0.005 min–1, which was more than 5 times higher than that of bare TiO2 nanotubes. Such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…In addition, the PEC activity of ms -BiVO 4 nanomaterials is largely impaired by persistent electron–hole recombination stemming from the low electron mobility (∼10 –2 cm 2 V –1 s –1 ), which reflects the strong electron–phonon coupling that leads to polaron formation around V 4+ sites . Intensive research efforts have been accordingly devoted to alleviate these shortcomings by metal doping , and heterostructuring in order to improve charge transport and separation of BiVO 4 nanomaterials for water oxidation and environmental remediation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the PEC activity of ms -BiVO 4 nanomaterials is largely impaired by persistent electron–hole recombination stemming from the low electron mobility (∼10 –2 cm 2 V –1 s –1 ), which reflects the strong electron–phonon coupling that leads to polaron formation around V 4+ sites . Intensive research efforts have been accordingly devoted to alleviate these shortcomings by metal doping , and heterostructuring in order to improve charge transport and separation of BiVO 4 nanomaterials for water oxidation and environmental remediation.…”
Section: Introductionmentioning
confidence: 99%
“…The EPR and XPS measurements (Figures and , respectively) did not reveal the presence of Ti 3+ , which would imply a negative shift in the Ti 2p BE and, as a consequence, an increase in the lattice parameters. ,,, In addition, this result is an indication that charge compensation in the TiO 2 -ACAC CTCs occurs predominantly through electronic compensation, which led to the formation of F + centers (eq and Figure ).…”
Section: Discussionmentioning
confidence: 93%
“…Around 30% TC abatement was observed for Black-TiO 2 nanotube arrays and a maximum TC photodegradation of ∼70% for a Black-TiO 2 nanotube array/BiVO 4 heterojunction after 6 h under visible-light radiation (300 W xenon lamp light with a 420 nm cutoff filter). 23 Ren et al 24 obtained a TC photocatalytic efficiency of ∼70% for a γ-Fe 2 O 3 /Black-TiO 2 heterojunction and ∼60% TC photocatalytic degradation for α-Fe 2 O 3 /Black-TiO 2 under visible-light excitation (300 W xenon lamp and an AM 1.5 filter) during 50 min. Another study on Black-TiO 2 heterojunctions revealed ∼88% TC degradation for Ag/La-Black-TiO 2 after 90 min of excitation at 300 W using a xenon lamp with a 420 nm cutoff filter (λ > 420 nm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining a doped semiconductor with another can change the photocatalyst reduction and oxidation driving forces along with the excited species charge separation. [17][18][19][20][21] Hence, a doped Ag 2 O material as a part of a composite should give an improved photocatalyst. There have been a few investigations on Ag 2 O-based composites (or photocatalytic heterostructures).…”
Section: Introductionmentioning
confidence: 99%